Making plant methane formation visible: insights from application of 13C-labeled dimethyl sulfoxide - Schroll, Moritz; Lenhart, Katharina; Greiner, Steffen; Keppler, Frank (Plant-environment interactions, 2022)
Methane (CH4) formation by vegetation has been studied intensively over the last 15 years. However, reported CH4 emissions vary by several orders of magnitude, thus making global estimates difficult. Moreover, the mechanism(s) for CH4 formation by plants is (are) largely unknown. Here, we introduce a new approach for making CH4 formation by plants clearly visible. By application of 13C-labeled dimethyl sulfoxide (DMSO) onto the leaves of tobacco plants (Nicotiana tabacum) and Chinese silver grass (Miscanthus sinensis) the effect of light and dark conditions on CH4 formation of this pathway was examined by monitoring stable carbon isotope ratios of headspace CH4 (δ13C-CH4 values). Both plant species showed increasing headspace δ13C-CH4 values while exposed to light. Higher light intensities increased CH4 formation rates in N. tabacum but decreased rates for M. sinensis. In the dark no formation of CH4 could be detected for N. tabacum, while M. sinensis still produced 50% of CH4 compared to that during light exposure. Our findings suggest that CH4 formation is clearly dependent on light conditions and plant species and thus indicate that DMSO is a potential precursor of vegetative CH4. The novel isotope approach has great potential to investigate, at high temporal resolution, physiological, and environmental factors that control pathway-specific CH4 emissions from plants.